Intravital Microscopic Evaluation of the Effects of a CXCR2 Antagonist in a Model of Liver Ischemia Reperfusion Injury in Mice - Oliveira, Thiago Henrique Caldeira de; Marques, Pedro Elias; Poosti, Fariba; Ruytinx, Pieter; Amaral, Flávio Almeida; Brandolini, Laura; Allegretti, Marcello; Proost, Paul; Teixeira, Mauro Martins (Frontiers in Immunology, 2018)
Background: Ischemia-reperfusion (IR) is a major contributor to graft rejection after liver transplantation. During IR injury, an intense inflammatory process occurs in the liver. Neutrophils are considered central players in the events that lead to liver injury. CXC chemokines mediate hepatic inﬂammation following reperfusion. However, few studies have demonstrated in real-time the behavior of recruited neutrophils. We used confocal intravital microscopy (IVM) to image neutrophil migration in the liver and to analyze in real-time parameters of neutrophil recruitment in the inflamed tissue in animals treated or not with reparixin, an allosteric antagonist of CXCR1/2 receptors. Material and Methods: WT and LysM-eGFP mice treated with reparixin or saline were subjected to 60 minutes of ischemia followed by different times of reperfusion. Mice received Sytox orange intravenously to show necrotic DNA in IVM. The effect of reparixin on parameters of local and systemic reperfusion-induced injury were also investigated. Results: Ischemia-reperfusion induced liver injury and inflammation, as evidenced by high levels of alanine aminotransferase (ALT) and myeloperoxidase (MPO) activity, chemokine and cytokine production and histological outcome. Treatment with reparixin significantly decreased neutrophil influx. Moreover, reparixin effectively suppressed the increase in serum concentrations of TNFα, IL-6 and CCL3, and the reperfusion-associated tissue damage. The number of neutrophils in the liver increased between 6h and 24h of reperfusion, whereas the distance traveled, velocity, neutrophil size and shape, and cluster formation reached a maximum 6h after reperfusion and then decreased gradually. In vivo imaging revealed that reparixin significantly decreased neutrophil infiltration and movement and displacement of recruited cells. Moreover, neutrophils had smaller size and less elongated shape in treated mice. Conclusions: Imaging of the liver by IVM was successfully implemented to describe neutrophil behavior in vivo during liver injury by IR. Treatment with reparixin decreased not only the recruitment of neutrophils in tissues but also their activation state and capacity to migrate within the liver. CXCR1/2 antagonists may be a promising therapy for patients undergoing liver transplantation. Keywords: Hepatic IR, chemokines, CXCR2, neutrophil-mediated liver injury.